Uji Aktivitas Antioksidan Ekstrak dan Fraksinasi Daun Tekelan (Chromolaena odorata (L.) R.M.King & H.Rob) Serta Uji Antibakteri Terhadap Staphylococcus aureus dan Escherichia coli - Anjarlit Romiyuliana Br Parapat; Ridwanto Ridwanto; Rafita Yuniarti; Zulmai Rani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Tekelan leaf (Chromolaena odorata (L.) R.M.King & H.Rob) is one of Indonesia's natural resources rich in bioactive compounds. Its traditional use for treating wounds, sore throats, diarrhea, and various other ailments is suspected to be linked to its antioxidant and antibacterial content. Objective: This research aimed to analyze the antioxidant activity of the ethanol extract, n-hexane fraction, and ethyl acetate fraction of tekelan leaves, and to test their antibacterial activity against Staphylococcus aureus and Escherichia coli. Method: The study used an experimental method. Antioxidant activity was tested using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method with a UV-Vis spectrophotometer, and the results were expressed as IC₅₀ values. The antibacterial test against S. aureus and E. coli was conducted using the disc diffusion method, and the inhibitory power was measured based on the inhibition zone diameter (mm). Results: The antioxidant test results showed that the ethanol extract and ethyl acetate fraction had strong activity with IC₅₀ values of 98.26 ppm and 75.43 ppm, respectively, while the n-hexane fraction showed weak activity (IC₅₀ 110.54 ppm). In the antibacterial test at a 40% concentration, the ethanol extract, n-hexane fraction, and ethyl acetate fraction inhibited the growth of both bacteria with strong to very strong categories. The highest average inhibition zones against E. coli and S. aureus were 19.03 mm and 21.36 mm (ethanol extract), 10.56 mm and 12.13 mm (n-hexane fraction), and 13.60 mm and 15.40 mm (ethyl acetate fraction), respectively. This activity was still lower than the positive control chloramphenicol, which produced inhibition zones of 28.23 mm (E. coli) and 27.43 mm (S. aureus). Conclusion: It was concluded that the extract and ethyl acetate fraction of tekelan leaves have strong antioxidant activity, while the n-hexane fraction is classified as weak. All samples (extract, n-hexane fraction, and ethyl acetate fraction) showed strong antibacterial activity against E. coli and S. aureus, although they have not matched the effectiveness of chloramphenicol.